2016
DOI: 10.5603/fm.a2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

Multiple variations in the course and motor branching pattern of the musculocutaneous nerve with unusual communication with the median nerve

Abstract: Anatomic variations in course and motor branching pattern of the musculocutaneous nerve (MCN) with unusual communication with the median nerve were (Folia Morphol 2016; 75, 4: 555-559)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Aydin et al found musculocutaneous nerve failure in a 58year-old male cadaver. They mention that the nerve supply to the biceps brachii and brachialis muscles came from two separate branches of the median nerve, one branch arose from the nerve trunk almost mid-arm, it was again divided into a motor branch to the brachialis muscle and a sensory branch giving sense of the lateral part of the forearm (11). A 43-year-old female cadaver presented with a complete bilateral absence of the musculocutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Aydin et al found musculocutaneous nerve failure in a 58year-old male cadaver. They mention that the nerve supply to the biceps brachii and brachialis muscles came from two separate branches of the median nerve, one branch arose from the nerve trunk almost mid-arm, it was again divided into a motor branch to the brachialis muscle and a sensory branch giving sense of the lateral part of the forearm (11). A 43-year-old female cadaver presented with a complete bilateral absence of the musculocutaneous nerves.…”
Section: Discussionmentioning
confidence: 99%